2019
DOI: 10.1016/j.compstruct.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of numerical modelling techniques for impact investigation on a wind turbine blade

Abstract: Wind turbine blades are exposed to numerous impact risks throughout their lifetimes. The impact risks range from bird collisions during operation to impacts with surrounding structures at the time of transportation and installation. Impact loads on the fibre composite blades can induce several complex, simultaneously interacting and visually undetectable damage modes and have a high potential to reduce the local and global blade sti↵ness. An assessment of such impact-induced damages is therefore necessary and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 40 publications
(73 reference statements)
0
23
0
Order By: Relevance
“…The utilised method also has demerits and can influence the results obtained for the impact response and impact resistance. In [26], it was found that shell-element based method overestimates the impact forces, and exhibited a relatively stiffer response compared to solid elements. Additionally, impact modelling of composites based on this technique could not discretely model an important failure mode for a composite sandwich structure, i.e., delamination and debonding of layers.…”
Section: Modelling Methodsmentioning
confidence: 99%
“…The utilised method also has demerits and can influence the results obtained for the impact response and impact resistance. In [26], it was found that shell-element based method overestimates the impact forces, and exhibited a relatively stiffer response compared to solid elements. Additionally, impact modelling of composites based on this technique could not discretely model an important failure mode for a composite sandwich structure, i.e., delamination and debonding of layers.…”
Section: Modelling Methodsmentioning
confidence: 99%
“…If the outcrossing rate is below the safe boundary, the mating operation is considered to a successful alignment; see Figure 2.5. The relative velocity influences the impact velocity, which may damage the guide pin (Verma et al 2018, Verma, Vedvik, Haselbach, Gao & Jiang 2019. There are two sorts of impact damages, i.e., the sideways impact and head-on impact; see Figure 2.6.…”
Section: Stages 2-4: Mating Problemmentioning
confidence: 99%
“…Abaqus/explicit (Hibbitt et al 2016) environment is chosen as the solver environment for impact analysis given that it is suited for non-linear problems involving large rotation, large displacements and complex interaction (Verma et al 2019e). The DTU 10 MW blade, which is based on shell-element is considered for impact assessment.…”
Section: Modelling and Analysis Of Blade Root Impact With Hubmentioning
confidence: 99%